Tobacco cessation behavior among smoking and smokeless form tobacco users in the indigenous population of Ernakulam, India - Eby Aluckal; Civy Pulayath; P Chithra; M S Balakrishna; Alexander M Luke; Simy Mathew (Wolters Kluwer Medknow Publications, 2020)
Purpose: Tobacco usage is the leading preventable cause of death in the world today. The tribes in Kuttampuzha region are the aboriginal tribal community found predominantly in the south Indian state of Kerala, India, and this study was conducted to identify tobacco cessation behavior in smoking and smokeless form of tobacco users among them. Materials and Methods: A cross-sectional design survey was conducted among 516 indigenous community people of Kuttampuzha area of Kerala, India, for the outcome of quit attempts made by the current tobacco users. The sociodemographic variables and tobacco user data collected were subjected to statistical analysis using Open Source R Software. Results: When considered the quit attempts among current smoking and smokeless form of tobacco users, a statistically significant difference was found in subjects who had quit attempts of 1 day or longer in the previous year (P = 0.01) than who were in groups of quit attempts more than 30 days or more than 6 months. Smokers had higher probability predicted of attempting quitting in comparison to smokeless form of tobacco users (odds ratio [OR] = 1.24, confidence interval [CI] = 1.09-1.39). The probability of doing a quit attempt was higher among users of tobacco who were having a comparatively higher socioeconomic status (OR = 1.30, CI = 1.12-1.48). Conclusion: This study provides useful insights into different determinants for quit attempts of tobacco users in South India, exploring the sociodemographic features of attempts to quit. International prevention and cessation initiatives will need to be customized to the social-cultural context of these primitive tribal areas of Kuttampuzha, Kerala, to help in prevention and cessation of tobacco usage.